Carpal-seminal biometrics, overcoming of dormancy and pre-germination treatments with GA(3) in Hymenaea courbaril L. (Fabaceae) - Pedroso-de-Moraes, Cristiano; Souza-Leal, Thiago de [UNESP]; Silveira, Paulo (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2018)
Aimed to perform carpal-seminal biometrics, compare techniques of scarification and analyze pre-germination treatments with GA(3) on Hymenaea courbaril. The seeds were subjected to 15, 30, 60, 90, 120, 150 and 180 minutes of scarification in lid, H2SO4, KOH and NaOH and with sandpaper. Scarified seeds were exposed to concentrations of 5, 10 and 20 mg.L-1 of GA(3) for 15, 30, 60, 90, 120, 150 and 180 minutes. Seeds were kept in an BOD under temperature of 25 degrees C and 116 mu mol.m(-2).s(-1) white light provided by fluorescent lamps. We calculated the germination rate (G.%) and emergence rate index (EVI). These indices were analyzed by polynomials regressions and ANOVA at 5 degrees/0. The morphometric characteristics can be used in generic taxonomic determinations and to choose propagation methods. The use of sulfuric acid for 30 minutes and scarification with sandpaper showed the best results for germination and emergence rate index, respectively.
Keywords: gibberellins; jatoba; plant propagation